Calculating global navigation satellite system satellite velocities and accelerations by utilizing the orbit fitting and orbit integration methods - Song, Chuanfeng (2024)
The high-precision satellite velocities and accelerations calculated by the Global Navigation Satellite System (GNSS) are essential for tasks such as airborne gravity data processing. Users generally interpolate satellite positions in the precise ephemeris to calculate satellite velocity and acceleration. However, due to the edge effect, the accuracy of the interpolation is relatively low near day boundaries. In this study, a method for calculating GNSS satellite velocity and acceleration based on orbit fitting and orbit integration was proposed, and the high-precision transformation relationship between satellite velocity and acceleration in the Earth-Centered Inertial (ECI) coordinate system and the Earth-Centered, Earth-Fixed (ECEF) coordinate system was derived. The experimental results show that the satellite velocity accuracy is 1.5 × 10−6 m/s and the acceleration accuracy is 1.0 × 10−8 m/s2 according to the proposed method. Thus, the proposed method improves the accuracy of calculating satellite velocity and acceleration near day boundaries, and helps GNSS users to obtain satellite velocity and acceleration information with consistent precision throughout the day.